GODS FROM THE DANUBE AREA: A CASE STUDY OF AN EXCEPTIONAL SNAKE VESSEL - Cvjetićanin, Tatjana (Rei Cretariae Romanae Fautorum Acta, 2024)
Among ceramic vessels and fragments in the Roman Collection of the National Museum in Belgrade one piece with distinctive decoration – applied zigzag snake-like ornament and medallions with female and male heads and animals – draws special attention.